2019
DOI: 10.1111/jfbc.12986
|View full text |Cite
|
Sign up to set email alerts
|

Dietary chia seeds (Salvia hispanica) improve acute dyslipidemia and steatohepatitis in rats

Abstract: Chia seeds (Salvia hispanica L.) are rich in omega fatty acids. Dyslipidemia and steatohepatitis are diseases that require effective treatments in obese and non‐obese patients. The aim was to evaluate the effect of chia intake on acute tyloxapol (TI)‐induced dyslipidemia, on acute carbon tetrachloride (TC)‐induced steatohepatitis, and on mixed damage (TC+TI) in non‐obese rats. Four experimental groups were fed for 4 weeks a diet with established rodent food (DE), and four groups were fed a diet with 15% added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 88 publications
1
15
0
3
Order By: Relevance
“…Dietary fiber, which is a form of carbohydrate, reduces the risk of atherosclerosis and CVD [27]. Several types of fatty acids and their intake also have different effects on lipid metabolism [28,29]. Moreover, according to Acosta-Navarro et al [30], higher consumption of an animal-based diet leads to higher TC levels.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fiber, which is a form of carbohydrate, reduces the risk of atherosclerosis and CVD [27]. Several types of fatty acids and their intake also have different effects on lipid metabolism [28,29]. Moreover, according to Acosta-Navarro et al [30], higher consumption of an animal-based diet leads to higher TC levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the essential oils and nonvolatile phenolic compounds (flavones, abietane diterpenes, and other simple phenolic compounds) that Salvia species contained have been used in Europe and many other countries as food preservatives because of their antibacterial and antioxidant properties (Bursal et al, 2019;Koubaa-Ghorbel, Chaabane, Turki, Makni-Ayadi, & El Feki, 2020). Scientific researches showed that the extracts prepared from Salvia species and their secondary metabolites (diterpenes, triterpenes, flavonoids) have many biological and pharmacological activities such as anti-inflammatory, hepatotoxic, cytotoxic, anticancer (El-Wakf, El-Habibi, Ali, Abd El-Ghany, & Elmougy, 2020;Fernndez-Martnez et al, 2019;Son, Oh, Choi, Han, & Kwon, 2005;Tayarani-Najaran, Asili, Aioubi, & Emami, 2013;Topcu, Ertaş, Kolak, Ozturk, & Ulubelen, 2007;Topcu et al, 2008). In a study reported by Son et al (2005), it was found that ferruginol, a diterpene containing phenol ring obtained from Salvia species, was effective against breast, colon, and lung cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Another alternative grain is chia ( Salvia hispanica L.; 18.0–21.5% protein content, approximately 25% fibre content), which is a staple food in Central American civilisations (Coelho & Salas‐Mellado, 2015; Ullah et al ., 2016). Chia seeds contain many vitamins, minerals, antioxidants (Knez Hrnčič et al ., 2020), polyunsaturated fatty acids (Reyes‐Caudillo et al ., 2008) and have also been found to decrease blood glucose and cholesterol levels, as well as decrease the incidence of diseases related to metabolic syndrome (Fernández‐Martínez et al ., 2019; Oh et al ., 2019). Chia seeds also contain adequate levels of all ten essential amino acids, including lysine, which tends to be an amino acid that is found in insufficient amounts in other grains (Graf et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%